Biological parameters and spawning potential ratio of Longtail Tuna Thunnus tonggol landed in Kranji fishing port, Lamongan District, Indonesia - LEDHYANE IKA HARLYAN; MUHAMMAD ARIF RAHMAN; MIHROBI KHALWATU RIHMI; SYA’DIYA FAHMA ARMI ABDILLAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Harlyan LI, Rahman MA, Rihmi MK, Abdillah SFA. 2023. Biological parameters and spawning potential ratio of Longtail Tuna Thunnus tonggol landed in Kranji fishing port, Lamongan District, Indonesia. Biodiversitas 24: 6527-6535. Longtail Tuna (Thunnus tonggol), one of the small-pelagic tropical fisheries in the Fisheries Management Area (FMA-712), is important in supporting global food security. Therefore, to ensure its sustainability, this fishery is applying for fishery certification to be an ecolabel fishery by the Marine Stewardship Council (MSC). However, limited information about Longtail Tuna's biological parameters and stock status in this management area will lead to failure in certification completion. This study aims to provide biological parameters and stock status of Longtail Tuna landed in the Kranji fishing port, Lamongan, Indonesia. Length, weight, and gonad weight of female Longtail Tuna individuals which landed in the Kranji fishing port were conducted from January to April 2023. Several analyses were carried out to figure out the biological parameters of Longtail Tuna, such as length-weight relationship, length at first maturity ( ) and length at first capture ( ) estimation. Length-Based Spawning Potential Ratio (LB-SPR) analysis was conducted to estimate fish exploitation. Results showed that the Longtail Tuna landing in the Kranji fishing port exhibited a negative allometric growth pattern with the length-weight relationship model W = 0.0433 FL2.7608. A comparison between  (43.9+0.11cm) and  (43.6+0.04cm) indicated that most female Longtail Tuna landed in the Kranji fishing port are mature (60% of the total samples). The LB-SPR analysis showed moderate exploitation status (SPR = 34%). Fishing activities are still manageable in this situation by focusing on stock sustainability. An overlapping fishing ground occurs in the Kranji water, showing the domination of two species landed in the Kranji fishing port, Longtail Tuna and Eastern Little Tuna (Euthynnus affinis). Therefore, Longtail Tuna fishery management might also consider fishery management of Eastern Little Tuna or other species with overlapped habitats.